Excavations at Tepe Guran, Luristan. Preliminary Report of the Danish Archaeological Expedition to Iran, 1963 - Meldgaard, Jørgen (1963)
I. Tepe Guran, and the early neolithic and bronze age of Northern Luristan, by J. Meldgaard. II. Early village-farming occupation, by P. Mortensen. III. The bronze age occupation and graves, by H. Thrane; ersch. 1964.